Development and characterization of nano-cream preparation containing natural extract using nanoemulsion techniques - Charoenkul, Kalyakorn; Phromyothin, Darinee (My University, 2017)
The objective of this study is to investigate the formulation, preparation and characterization of nano-cream from squalene in olive oil, virgin coconut oil and turmeric using nanoemulsion techniques. The 'shock method' via a phase inversion temperature (PIT) was prepared the nanoemulsion which was kinetically stable system, comprised of oil droplets dispersed in aqueous media using tween 80 and span 80 as emulsifier and stabilized by nonylphenol ethoxylate as surfactant, respectively. Characterization and evaluation were generally carried out by preliminary characterization, pH, conductivity, determinations of particle size and thermal stability. The obtained nanoemulsion from squalene and virgin coconut oil with the ratio 0.5:3.6 was cloudy white color with an average particle size of 400 nm and stable without any phase separation. Nanoemulsions with the addition of turmeric were opaque yellow and particle size is found to decrease to 200 nm.
Keywords: Nanoemulsions; Phase Inversion Temperature; Squalene; Turmeric; Virgin Coconut Oil